Developing Educators for the Digital Age - Breen, Paul (University of Westminster Press, 2025)
Evaluating skills and knowledge capture lies at the cutting edge of contemporary higher education where there is a drive towards increasing evaluation of classroom performance and use of digital technologies in pedagogy. Developing Educators for the Digital Age is a book that provides a narrative account of teacher development geared towards the further usage of technologies (including iPads, MOOCs and whiteboards) in the classroom presented via the histories and observation of a diverse group of teachers engaged in the multiple dimensions of their profession. Drawing on the insights of a variety of educational theories and approaches (including TPACK) it presents a practical framework for capturing knowledge in action of these English language teachers – in their own voices – indicating how such methods, processes and experiences shed light more widely on related contexts within HE and may be transferable to other situations. This book will be of interest to the growing body of scholars interested in TPACK theory, or communities of practice theory and more widely anyone concerned with how new pedagogical skills and knowledge with technology may be incorporated in better practice and concrete instances of teaching.